Expression and T cell regulatory action of the PD‐1 immune checkpoint in the ovary and fallopian tube. (26th December 2022) - Johnson, Joshua; Kim, So‐Youn; Sam, Peter Ka; Asokan, Rengasamy; Cari, Evelyn Llerena; Bales, Elise S.; Luu, Thanh‐Ha; Perez, Lauren; Kallen, Amanda N.; Nel‐Themaat, Liesl; Polotsky, Alex J.; Post, Miriam D.; et al.
Abstract: Problem: Immune cell trafficking and surveillance within the ovary and fallopian tube are thought to impact fertility and also tumorigenesis in those organs. However, little is known of how native cells of the ovary and fallopian tube interact with resident immune cells. Interaction of the Programmed Cell Death Protein‐1 (PD‐1/PDCD‐1/CD279) checkpoint with PD‐L1 is associated with downregulated immune response. We have begun to address the question of whether PD‐1 ligand or its receptors (PD‐L1/‐L2) can regulate immune cell function in these tissues of the female reproductive tract. Method of study: PD‐1 and ligand protein expression was evaluated in human ovary and fallopian tube specimens, the latter of which included stages of tubal cell transformation and early tumorigenesis. Ovarian expression analysis included the determination of the proteins in human follicular fluid (HFF) specimens collected during in vitro fertilization procedures. Finally, checkpoint bioactivity of HFF was determined by treatment of separately‐isolated human T cells and the measurement of interferon gamma (IFNγ). Results: We show that membrane bound and soluble variants of PD‐1 and ligands are expressed by permanent constituent cell types of the human ovary and fallopian tube, including granulosa cells and oocytes. PD‐1 and soluble ligands were present in HFF at bioactive levels that control T cell PD‐1 activation and IFNγ production; full‐length checkpoint proteins were found to be highly enriched in HFF exosome fractions. Conclusion: The detection of PD‐1 checkpoint proteins in the human ovary and fallopian tube suggests that the pathway is involved in immunomodulation during folliculogenesis, the window of ovulation, and subsequent egg and embryo immune‐privilege. Immunomodulatory action of receptor and ligands in HFF exosomes is suggestive of an acute checkpoint role during ovulation. This is the first study in the role of PD‐1 checkpoint proteins in human tubo‐ovarian specimens and the first examination of its potential regulatory action in the contexts of normal and assisted reproduction.